Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Assessing the risk of climate maladaptation for Canadian polar bears - L. Ruth Rivkin; Evan S. Richardson; Joshua M. Miller; Todd C. Atwood; Steven Baryluk; Erik W. Born; Corey Davis; Markus Dyck; Evelien de Greef; Kristin L. Laidre; Nicholas J. Lunn; Sara McCarthy; et al. (Ecology Letters, 2024)
The Arctic is warming four times faster than the rest of the world, threatening the persistence of many Arctic species. It is uncertain if Arctic wildlife will have sufficient time to adapt to such rapidly warming environments. We used genetic forecasting to measure the risk of maladaptation to warming temperatures and sea ice loss in polar bears ( Ursus maritimus ) sampled across the Canadian Arctic. We found evidence for local adaptation to sea ice conditions and temperature. Forecasting of genome‐environment mismatches for predicted climate scenarios suggested that polar bears in the Canadian high Arctic had the greatest risk of becoming maladapted to climate warming. While Canadian high Arctic bears may be the most likely to become maladapted, all polar bears face potentially negative outcomes to climate change. Given the importance of the sea ice habitat to polar bears, we expect that maladaptation to future warming is already widespread across Canada.

Development of an 8K SNP chip to assess adaptive diversity and hybridization in polar bears - Joshua M. Miller; René M. Malenfant; L. Ruth Rivkin; Todd C. Atwood; Steven Baryluk; Erik W. Born; Rune Dietz; Kristin L. Laidre; Jodie Pongracz; Evan S. Richardson; Øystein Wiig; Corey S. Davis (Conservation Genetics Resources, 2024)
The polar bear ( Ursus maritimus ) is a species particularly vulnerable to the effects of climate change. As the climate warms, polar bears will be forced to move to more suitable habitats which are likely to shrink, adapt to the new conditions, or decline in population size. However, the genomic diversity within and among all 19 subpopulations of polar bears, and therefore their adaptive potential, is currently unknown. In addition, warmer climates are likely to result in more frequent contact between polar bears and grizzly bears ( U. arctos ), with which they can hybridize. Here we describe the development, quality control, and application of the Ursus maritimus V2 SNP chip. This 8 K SNP chip contains loci explicitly selected to assess both RAD-derived and transcriptome-derived loci, as well as SNPs to detect hybridization between species. A total of 7,239 loci (90.3% of those printed) were successfully genotyped, with over 99% genotype concordance for individuals typed in duplicate on this chip, and between individuals typed here and on the Ursus maritimus V1 SNP chip. Using simulations, we demonstrate that the markers have high accuracy and efficiency to detect hybridization and backcrosses between polar bears and grizzly bears. However, empirical analysis of 371 polar bears, 440 grizzly bears, and 8 known hybrids found no novel instances of recent hybridization. The Ursus maritimus V2 SNP chip provides a powerful tool for monitoring the adaptive potential of this species along with assessing population structure, quantitative genomics, and hybridization in polar bears.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Re-Envisioning Undergraduate Research Experiences to Increase Diversity, Equity, and Inclusion, and Harness the Power of Diversity in Ocean Sciences - Paul Barber; Catalina Martinez; Corey Garza; Deidre Gibson; Alexandra Davis (Oceanography, 2023)
Diversity in ocean sciences lags far behind US demographics. A substantial body of research highlights barriers that limit the participation and success of students from underrepresented minoritized (URM) and other marginalized groups in STEM disciplines, and a wealth of studies highlight successful interventions that improve the persistence of these groups in STEM higher education. Despite this knowledge, over the past four decades, ocean sciences has made limited progress in growing diversity within its workforce, suggesting new strategies are needed. Undergraduate research experiences are a pivotal pathway toward graduate education and future careers in ocean sciences, but they are plagued by many issues that limit the participation and success of persons from URM and other marginalized backgrounds. Here we summarize obstacles that limit participation of diverse populations in ocean sciences and highlight successful strategies for overcoming these obstacles. By re-envisioning how we approach undergraduate research experiences and bringing intentionality to the recruitment of students and the training environments that they experience, we can more effectively grow diversity in ocean sciences and unleash the power of diversity to address the pressing local and global problems facing marine ecosystems.

Mitigation of cadmium uptake in Theobroma cacao L: efficacy of soil application methods of hydrated lime and biochar - Gideon Ramtahal; Pathmanathan Umaharan; Carisa Davis; Corey Roberts; Anand Hanuman; Leon Ali (Plant and Soil, 2022)

Genetic management on the brink of extinction: sequencing microsatellites does not improve estimates of inbreeding in wild and captive Vancouver Island marmots (Marmota vancouverensis) - Kimberley G. Barrett; Geneviève Amaral; Melanie Elphinstone; Malcolm L. McAdie; Corey S. Davis; Jasmine K. Janes; John Carnio; Axel Moehrenschlager; Jamieson C. Gorrell (Conservation Genetics, 2022)
Captive breeding is often a last resort management option in the conservation of endangered species which can in turn lead to increased risk of inbreeding depression and loss of genetic diversity. Thus, recording breeding events via studbook for the purpose of estimating relatedness, and facilitating mating pair selection to minimize inbreeding, is common practice. However, as founder relatedness is often unknown, loss of genetic variation and inbreeding cannot be entirely avoided. Molecular genotyping is slowly being adopted in captive breeding programs, however achieving sufficient resolution can be challenging in small, low diversity, populations. Here, we evaluate the success of the Vancouver Island marmot ( Marmota vancouverensis ; VIM; among the worlds most endangered mammals) captive breeding program in preventing inbreeding and maintaining genetic diversity. We explored the use of high-throughput amplicon sequencing of microsatellite regions to assay greater genetic variation in both captive and wild populations than traditional length-based fragment analysis. Contrary to other studies, this method did not considerably increase diversity estimates, suggesting: (1) that the technique does not universally improve resolution, and (2) VIM have exceedingly low diversity. Studbook estimates of pairwise relatedness and inbreeding in the current population were weakly, but positively, correlated to molecular estimates. Thus, current studbooks are moderately effective at predicting genetic similarity when founder relatedness is known. Finally, we found that captive and wild populations did not differ in allelic frequencies, and conservation efforts to maintain diversity have been successful with no significant decrease in diversity over the last three generations.

Evaluation of novel genomic markers for pedigree construction in an isolated population of Weddell Seals (Leptonychotes weddellii) at White Island, Antarctica - Joshua M. Miller; Erin O. Campbell; Jay J. Rotella; Kaitlin R. Macdonald; Thomas S. Gelatt; Corey S. Davis (Conservation Genetics Resources, 2022)

Lower cardiac output is associated with neurodegeneration among older adults with normal cognition but not mild cognitive impairment - Elizabeth E. Moore; Dandan Liu; Corey W. Bown; Hailey A. Kresge; Deepak K. Gupta; Kimberly R. Pechman; Lisa A. Mendes; L. Taylor Davis; Katherine A. Gifford; Adam W. Anderson; Thomas J. Wang; Bennett A. Landman; et al. (Brain Imaging and Behavior, 2021)

Gene flow and climate‐associated genetic variation in a vagile habitat specialist - Zachary G. MacDonald; Julian R. Dupuis; Corey S. Davis; John H. Acorn; Scott E. Nielsen; Felix A. H. Sperling (Molecular Ecology, 2020)
Previous work in landscape genetics suggests that geographic isolation is of greater importance to genetic divergence than variation in environmental conditions. This is intuitive when configurations of suitable habitat are a dominant factor limiting dispersal and gene flow, but has not been thoroughly examined for habitat specialists with strong dispersal capability. Here, we evaluate the effects of geographic and environmental isolation on genetic divergence for a vagile invertebrate with high habitat specificity and a discrete dispersal life stage: Dod's Old World swallowtail butterfly, Papilio machaon dodi . In Canada, P. m. dodi are generally restricted to eroding habitat along major river valleys where their larval host plant occurs. A series of causal and linear mixed effects models indicate that divergence of genome‐wide single nucleotide polymorphisms is best explained by a combination of environmental isolation (variation in summer temperatures) and geographic isolation (Euclidean distance). Interestingly, least‐cost path and circuit distances through a resistance surface parameterized as the inverse of habitat suitability were not supported. This suggests that, although habitat associations of many butterflies are specific due to reproductive requirements, habitat suitability and landscape permeability are not equivalent concepts due to considerable adult vagility. We infer that divergent selection related to variation in summer temperatures has produced two genetic clusters within P. m. dodi , differing in voltinism and diapause propensity. Within the next century, temperatures are predicted to rise by amounts greater than the present‐day difference between regions of the genetic clusters, potentially affecting the persistence of the northern cluster under continued climate change.

Climate change lengthens southeastern USA lightning‐ignited fire seasons - Jennifer M. Fill; Corey N. Davis; Raelene M. Crandall (Global Change Biology, 2019)
Trends in average annual or seasonal precipitation are insufficient for detecting changes in the climatic fire season, especially in regions where the fire season is defined by wet–dry seasonal cycles and lightning activity. Using an extensive dataset (1897–2017) in the Coastal Plain of the southeastern United States, we examined changes in annual dry season length, total precipitation, and (since 1945) the seasonal distribution of thunder‐days as a correlate of lightning activity. We found that across the entire region, the dry season has lengthened by as much as 156 days (130% over 120 years), both starting earlier and ending later with less total precipitation. Less rainfall over a longer dry season, with no change in seasonal thunderstorm patterns, likely increases both the potential for lightning‐ignited wildfires and fire severity. Global climate change could be having a hitherto undetected influence on fire regimes by altering the synchrony of climatic seasonal parameters.

Management implications of highly resolved hierarchical population genetic structure in thinhorn sheep - Zijian Sim; Corey S. Davis; Bill Jex; Troy Hegel; David W. Coltman (Conservation Genetics, 2019)

Delimitation of Alosa species (Teleostei: Clupeiformes) from the Sea of Azov: integrating morphological and molecular approaches - Oksana V. Vernygora; Corey S. Davis; Alison M. Murray; Felix A. H. Sperling (Journal of Fish Biology, 2018)
Shads of the genus Alosa are essential to commercial fisheries across North America and Europe, but in some areas their species boundaries remain controversial. Traditional morphology‐based taxonomy of Alosa spp. has relied heavily on the number of gill rakers and body proportions, but these can be highly variable. We use mitochondrial (mt)DNA ( coI and cytb ) and genome‐wide single nucleotide polymorphisms (SNP) along with morphological characters to assess differentiation among endemic Ponto‐Caspian shads in the Sea of Azov. Morphological species assignments based on gill‐raker number were not congruent with genetic lineages shown by mtDNA and SNPs. Iterative analysis revealed that genetic lineages were associated with sampling location and several other morphometric traits (caudal peduncle depth, pre‐anal length and head length). Phylogenetic analysis of the genus placed Ponto‐Caspian Alosa spp. in the same evolutionary lineage as endangered Alosa spp. endemic to Greece, highlighting the importance of these findings to conservation management. We conclude that gill‐raker number is not reliable for delimiting species of Alosa. This taxonomic uncertainty should be addressed by examining type material to provide a robust integrative classification for these commercially important fishes.

Riverscape genetic structure of a threatened and dispersal limited freshwater species, the Rocky Mountain Sculpin (Cottus sp.) - Jonathan L. W. Ruppert; Patrick M. A. James; Eric B. Taylor; Tyana Rudolfsen; Marie Veillard; Corey S. Davis; Doug Watkinson; Mark S. Poesch (Conservation Genetics, 2017)

The nociceptive withdrawal response of the foot in the spinalized rat exhibits limited dependence on stimulus location - Corey L. Cleland; Craig E. Esquivel; Heath T. Davis (Experimental Brain Research, 2017)

Clones or clans: the genetic structure of a deep‐sea sponge, Aphrocallistes vastus, in unique sponge reefs of British Columbia, Canada - Rachel R. Brown; Corey S. Davis; Sally P. Leys (Molecular Ecology, 2017)
Understanding patterns of reproduction, dispersal and recruitment in deep‐sea communities is increasingly important with the need to manage resource extraction and conserve species diversity. Glass sponges are usually found in deep water (>1000 m) worldwide but form kilometre‐long reefs on the continental shelf of British Columbia and Alaska that are under threat from trawling and resource exploration. Due to their deep‐water habitat, larvae have not yet been found and the level of genetic connectivity between reefs and nonreef communities is unknown. The genetic structure of Aphrocallistes vastus , the primary reef‐building species in the Strait of Georgia (SoG) British Columbia, was studied using single nucleotide polymorphisms ( SNP s). Pairwise comparisons of multilocus genotypes were used to assess whether sexual reproduction is common. Structure was examined 1) between individuals in reefs, 2) between reefs and 3) between sites in and outside the SoG. Sixty‐seven SNP s were genotyped in 91 samples from areas in and around the SoG, including four sponge reefs and nearby nonreef sites. The results show that sponge reefs are formed through sexual reproduction. Within a reef and across the SoG basin, the genetic distance between individuals does not vary with geographic distance ( r = −0.005 to 0.014), but populations within the SoG basin are genetically distinct from populations in Barkley Sound, on the west coast of Vancouver Island. Population structure was seen across all sample sites (global F ST = 0.248), especially between SoG and non‐SoG locations (average pairwise F ST = 0.251). Our results suggest that genetic mixing occurs across sponge reefs via larvae that disperse widely.

Genetic diversity and population structure identify the potential source of the invasive red clover casebearer moth, Coleophora deauratella, in North America - Boyd A. Mori; Corey S. Davis; Maya L. Evenden (Biological Invasions, 2016)

Evidence of adoption, monozygotic twinning, and low inbreeding rates in a large genetic pedigree of polar bears - René M. Malenfant; David W. Coltman; Evan S. Richardson; Nicholas J. Lunn; Ian Stirling; Elizabeth Adamowicz; Corey S. Davis (Polar Biology, 2016)

Limited genetic structure in a wood frog (Lithobates sylvaticus) population in an urban landscape inhabiting natural and constructed wetlands - Benjamin L. S. Furman; Brett R. Scheffers; Murdoch Taylor; Corey Davis; Cynthia A. Paszkowski (Conservation Genetics, 2016)

Isolation and characterization of 8 polymorphic microsatellite markers from the Greater Short-horned Lizard (Phrynosoma hernandesi) - Zijian Sim; Brandon K. Booker; Michelle Viengkone; Corey S. Davis; Magdalene N.-Y. Leung; Anthony P. Russell; Cynthia A. Paszkowski (Conservation Genetics Resources, 2014)

SNP discovery in a reef-forming glass sponge, Aphrocallistes vastus, using the Ion Torrent next generation sequencing platform - Rachel R. Brown; Corey S. Davis; Sally P. Leys (Conservation Genetics Resources, 2014)

Apodemia mormo in Canada: population genetic data support prior conservation ranking - Benjamin Proshek; Lindsay A. Crawford; Corey S. Davis; Sylvie Desjardins; Allison E. Henderson; Felix A. H. Sperling (Journal of Insect Conservation, 2013)

Development of eight microsatellite loci from the endangered huemul (Hippocamelus bisulcus) and cross-species amplification in six other ungulate species - Aaron B. A. Shafer; Paulo Corti; David W. Coltman; Juan Carlos Marín; Corey S. Davis (Conservation Genetics Resources, 2012)

Identification and characterization of 16 single nucleotide polymorphisms (SNPs) in the northeast intertidal gooseneck barnacle, Pollicipes polymerus - Marjan Barazandeh; Corey S. Davis (Conservation Genetics Resources, 2012)

Spatial genetic structure of the mountain pine beetle ( Dendroctonus ponderosae ) outbreak in western Canada: historical patterns and contemporary dispersal - G. D. N. GAYATHRI SAMARASEKERA; NICHOLAS V. BARTELL; B. STAFFAN LINDGREN; JANICE E. K. COOKE; COREY S. DAVIS; PATRICK M. A. JAMES; DAVID W. COLTMAN; KAREN E. MOCK; BRENT W. MURRAY (Molecular Ecology, 2012)
Environmental change has a wide range of ecological consequences, including species extinction and range expansion. Many studies have shown that insect species respond rapidly to climatic change. A mountain pine beetle epidemic of record size in North America has led to unprecedented mortality of lodgepole pine, and a significant range expansion to the northeast of its historic range. Our goal was to determine the spatial genetic variation found among outbreak population from which genetic structure, and dispersal patterns may be inferred. Beetles from 49 sampling locations throughout the outbreak area in western Canada were analysed at 13 microsatellite loci. We found significant north‐south population structure as evidenced by: (i) Bayesian‐based analyses, (ii) north‐south genetic relationships and diversity gradients; and (iii) a lack of isolation‐by‐distance in the northernmost cluster. The north‐south structure is proposed to have arisen from the processes of postglacial colonization as well as recent climate‐driven changes in population dynamics. Our data support the hypothesis of multiple sources of origin for the outbreak and point to the need for population specific information to improve our understanding and management of outbreaks. The recent range expansion across the Rocky Mountains into the jack/lodgepole hybrid and pure jack pine zones of northern Alberta is consistent with a northern British Columbia origin. We detected no loss of genetic variability in these populations, indicating that the evolutionary potential of mountain pine beetle to adapt has not been reduced by founder events. This study illustrates a rapid range‐wide response to the removal of climatic constraints, and the potential for range expansion of a regional population.

A phylogenetic investigation of Carthamus combining sequence and microsatellite data - Victoria G. Bowles; Reinhold Mayerhofer; Corey Davis; Allen G. Good; Jocelyn C. Hall (Plant Systematics and Evolution, 2010)

History and fate of a small isolated population of Weddell seals at White Island, Antarctica - Thomas S. Gelatt; Corey S. Davis; Ian Stirling; Donald B. Siniff; Curtis Strobeck; Isabelle Delisle (Conservation Genetics, 2010)

Population structure of ice‐breeding seals - COREY S. DAVIS; IAN STIRLING; CURTIS STROBECK; DAVID W. COLTMAN (Molecular Ecology, 2008)
The development of population genetic structure in ice‐breeding seal species is likely to be shaped by a combination of breeding habitat and life‐history characteristics. Species that return to breed on predictable fast‐ice locations are more likely to exhibit natal fidelity than pack‐ice‐breeding species, which in turn facilitates the development of genetic differentiation between subpopulations. Other aspects of life history such as geographically distinct vocalizations, female gregariousness, and the potential for polygynous breeding may also facilitate population structure. Based on these factors, we predicted that fast‐ice‐breeding seal species (the Weddell and ringed seal) would show elevated genetic differentiation compared to pack‐ice‐breeding species (the leopard, Ross, crabeater and bearded seals). We tested this prediction using microsatellite analysis to examine population structure of these six ice‐breeding species. Our results did not support this prediction. While none of the Antarctic pack‐ice species showed statistically significant population structure, the bearded seal of the Arctic pack ice showed strong differentiation between subpopulations. Again in contrast, the fast‐ice‐breeding Weddell seal of the Antarctic showed clear evidence for genetic differentiation while the ringed seal, breeding in similar habitat in the Arctic, did not. These results suggest that the development of population structure in ice‐breeding phocid seals is a more complex outcome of the interplay of phylogenetic and ecological factors than can be predicted on the basis of breeding substrate and life‐history characteristics.

Male-biased sex ratios in New Zealand fur seal pups relative to environmental variation - Corey J. A. Bradshaw; Robert G. Harcourt; Lloyd S. Davis (Behavioral Ecology and Sociobiology, 2003)

The winter migration of Adelie penguins breeding in the Ross Sea sector of Antarctica - Lloyd Davis; Robert Harcourt; Corey Bradshaw (Polar Biology, 2001)